1973
DOI: 10.1002/zaac.19733950210
|View full text |Cite
|
Sign up to set email alerts
|

Zur Struktur des Cr3O‐Ions in β‐Cs2Cr3O10

Abstract: β‐Cs2Cr3O10 kristallisiert rhomboedrisch in der Raumgruppe R3c mit a = 14,751 Å und α = 49,52°. Die Bindungslängen CrO in Cr3O 210 betragen 1,62 bzw. 1,57 Å in den CrO3‐Gruppen bzw. den CrO2‐Gruppen (Mittelwerte), sowie 1,63 – 1,93 Å in den CrO‐Brücken, wobei die beiden äußeren Bindungen um 0,1–0,2 Å langer sind als die vom mittleren Cr‐Atom ausgehenden. Die Bindungswinkel am Sauerstoffatom betragen 123° und 139°. Die Schwingungsspektren der höheren Polychromate werden im Zusammenhang mit ihrer Struktur disk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

1973
1973
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
6
0
4
Order By: Relevance
“…A ce jour, les structures des tripolychromates suivants ont 6t~ d&ermin6es: (NHa)2Cr30~0, orthorhombique Pbca (Seiter, 1957), Cs2Cr3Ol0 fl, trigonal R3c (Mattes & Meschede, 1973), Rb2CraOl0, isomorphe de (NHa)2Cr~O~0 (L6fgren, 1974), (CN~H6)2Cr30~0, monoclinique C2/c (St~piefi & Grabowski, 1977). D'apr+s Mattes & Meschede (1973), il existe 6galement une forme a de Cs2Cr30~0, isomorphe de (N Ha)2Cr3010.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…A ce jour, les structures des tripolychromates suivants ont 6t~ d&ermin6es: (NHa)2Cr30~0, orthorhombique Pbca (Seiter, 1957), Cs2Cr3Ol0 fl, trigonal R3c (Mattes & Meschede, 1973), Rb2CraOl0, isomorphe de (NHa)2Cr~O~0 (L6fgren, 1974), (CN~H6)2Cr30~0, monoclinique C2/c (St~piefi & Grabowski, 1977). D'apr+s Mattes & Meschede (1973), il existe 6galement une forme a de Cs2Cr30~0, isomorphe de (N Ha)2Cr3010.…”
Section: Introductionunclassified
“…D'apr+s Mattes & Meschede (1973), il existe 6galement une forme a de Cs2Cr30~0, isomorphe de (N Ha)2Cr3010.…”
Section: Introductionunclassified
“…K 2 Cr 3 O 10 , on the other hand, is monoclinic (space group P2 1 /n; Soldatov et al, 1978;Blum et al, 1979). Among these trichromates, a second, hexagonal modi®cation (space group P6 3 /m) is also known to exist for the NH 4 (Blum & Guitel, 1980) and Rb members (Blum, 1979), whereas a rhombohedral modi®cation (space group R3c) was determined only for Cs 2 Cr 3 O 10 (-Cs 2 Cr 3 O 10 ; Mattes & Meschede, 1973). The latter authors also reported the existence of orthorhombic -Cs 2 Cr 3 O 10 and that it is probably isotypic with (NH 4 ) 2 Cr 3 O 10 (Seiter, 1957); this assumption is con®rmed by the present study.…”
Section: Commentmentioning
confidence: 99%
“…Le trichromate d'ammonium (NH4)2Cr3Ol0 est d6j/l connu sous une forme cristallisant dans le groupe orthorhombique Pbca, et dont la structure, d&ermin6e par Seiter (1957), est ~galement adopt6e par a-CsECr30~o (Mattes & Meschede, 1973) et RbECr3Olo (L6fgren, 1974).…”
Section: R6f6reneesunclassified
“…Nous avons 6tudi~ une seconde forme de (NH4)2Cr3Ol0, cristallisant dans le groupe hexagonal P63/m et dont la structure pr6sente des analogies avec celle de fl-Cs2Cr30~0, trigonale R3c (Mattes & Meschede, 1973).…”
Section: R6f6reneesunclassified